Understanding regression analysis : an introductory guide - Schroeder, Larry D.; Sjoquist, David L. (Quantitative applications in the social sciences, 2017)
The second edition of Understanding Regression Analysis: An Introductory Guide presents the fundamentals of regression analysis, from its meaning to uses, in a concise, easy-to-read, and non-technical style. From back cover